Health conditions, health literacy, access to care, and health care experiences among lesbian, gay, bisexual, transgender and queer adults in Lebanon - Wassim Daoud Khatoun; Ali Slim; Jana Makhlouf; Sam S. S. Lau; Marco C. H. Cheng; Alissa Chebat; Michel Boustany; Elio Tahan; Carmel Bouclaous (International Journal for Equity in Health)
Abstract Background This study aims to assess the physical health of individuals belonging to the lesbian, gay, bisexual, transgender, and queer (LGBTQ) community, considering health system challenges like access to care and patient experiences and community-specific attributes like health literacy and self-acceptance. Methods This cross-sectional study was conducted in January-June 2022 using non-probabilistic sampling. The survey collected sociodemographic characteristics, information on access to care and patient experiences, prevalence of chronic conditions, sexually transmitted infections (STIs), and health literacy levels. The inclusion criteria required participants to be of Lebanese nationality, at least 18 years old, and to identify as part of the LGBTQ community. Descriptive statistics summarized the data. Two sample t-tests and chi-square tests were used to examine associations between variables. Results A total of 496 participants took the survey, with a majority identifying as bisexual (38.5%) or gay (35.1%). Around 41.1% reported at least one chronic condition. Difficulty accessing healthcare was experienced by 37.7%, with 11.1% reporting a negative patient experience. Participants who reported experiencing discrimination were significantly more likely to delay seeking health services (p < 0.001), with transgender-identifying participants experiencing significantly more discrimination that non-transgender-identifying participants. Regarding sexual health, 15.7%, of those who tested, reported at least one STI. Their preferred testing sites were Non-Governmental Organizations (59.3%). Adequate health literacy level was significantly associated with STI testing (t = 3.34, p < 0.01) and chronic disease (t = 3.76, p < 0.01). Conclusion Our findings underscore the importance of inclusive healthcare policies that address discriminatory experiences in healthcare settings and the need for targeted evidence-based interventions to improve health outcomes among LGBTQ individuals.